Pirates and Emperors, old & new International Terrorism in the Real World - Chomsky, Noam (New Delhi Viva books, 2007)
'Judged in terms of the power, range, novelty, and influence of his thought, Noam Chomsky is arguably the most important intellectual alive.' New York Times Book Review One of the radical heroes of our age ... A towering intellect ... Powerful, always provocative.' Guardian 'Our greatest unraveller of accredited lies.' New Statesman 'An exploder of received truths.' New York Times 'On the one hand we have the established media, the respectable community of foreign affairs analysts, the government?and on the other, Noam Chomsky.' The Nation 'Thank God for Noam Chomsky.' Robert Fisk, The Independent This new, fully updated edition of Chomsky's classic dissection of terrorism explores the role of the US in the Middle East and reveals how the media are used to manipulate public opinion about what constitutes 'terrorism'. With several new chapters on the global crisis stemming from the events of September 11, as well as the original sections on Iran and the bombing of Libya, this is a brilliant account of the workings of state terrorism by the world's foremost critic of US imperialism. New chapters cover the second Palestinian Intifada - or War of Stones - that began in October 2000; A detailed account of the impact that September 11 has had on US foreign policy in the Middle East; Chomsky's deconstruction of depictions and perceptions of terrorism since September 11.
Keywords: Terrorism